Understanding students’ spending behaviour: Integrating financial literacy, economic factors and lifestyle influence - Zahari, Nor Sabrina; Zahari, Mohd Fahmi; Mohd Hassan, Norsilawati; Ab Rani, Nor Zuriati Amani; Nik Hassan, Nik Suriati (Journal of Islamic, Social, Economics and Development, 2026)
This study investigates the spending behavior of students at UiTM Kelantan, focusing on the impact of five potential determinants: financial literacy, price elasticity, habit/personal interest, family income, and social media influence. A total of 144 students participated, and data were analyzed using multiple regression analysis to identify significant predictors of spending behavior. The results indicate that financial literacy, price elasticity, and habit/personal interest significantly influence students’ spending patterns, while family income and social media exposure were not significant. These findings highlight the importance of enhancing financial literacy and understanding personal consumption habits to promote responsible spending among students.